P01.054 Patterns of first tumor progression and impact on survival of salvage therapies in low-grade gliomas following initial chemotherapy with temozolomide. (19th September 2018) - Pellerino, A; Rudà, R; Pace, A; Carapella, C; Dealis, C; Caroli, M; Faedi, M; Bello, L; Soffietti, R
Abstract: Background: Initial chemotherapy with temozolomide (TMZ) has been suggested to provide some benefit in terms of response and progression-free survival (PFS) in high-risk low-grade gliomas. To date, no standard treatment has been validated at progression. The aim of the study was to investigate which is the optimal salvage therapy after the first progression and the factors that may influence the PFS and the overall survival (OS). Material and Methods: We evaluated 49 patients with an histological diagnosis of grade II oligodendroglioma and oligoastrocytoma according to WHO 2007 included in a phase II AINO (Italian Association for Neuro-Oncology) trial, who progressed following initial chemotherapy alone with dose-dense TMZ. Fifteen patients (30.6%) had seizures at the time of progression. Molecular data were available in 48 patients: 29 patients were IDH 1/2 mutated, 23 1p/19q codeleted, and 36 MGMT methylated. Median follow up was 140 months. Results: All patients had local tumor progression and patterns on MRI were as follows: a FLAIR lesion in 25 patients (51.0%), a mild patchy enhancing lesion in 14 patients (28.6%), and a nodular enhancing lesion in the other 10 patients (20.4%). Twenty-four patients (49%) underwent a second-line chemotherapy (TMZ rechallenge or PCV schedule), 12 patients (24.5%) a salvage radiotherapy, 11 patients (22.4%) a second surgery (10 gross-total resection and 1 subtotal resection), while 2 patients (4.1%) received palliative care. The response rate (RANO criteria) following salvage radiotherapy or chemotherapy was as follows: PR in 6/38 patients (15.8%), MR in 9/38 (23.7%), SD in 10/38 (26.3%), and PD in 13/38 (34.2%). Overall, median PFS after first salvage therapy was 18 months (IC95% 11–27). Median PFS was 11 months (IC95% 8–74) after radiotherapy, 14 months after chemotherapy and 31 months after surgery (IC95% 18–51, p 0.013). Median OS from the first salvage therapy was 63 months (IC95% 4 - non reached). Median OS was 44 months (IC95% 4 - not reached) after radiotherapy, 38 months (IC95% 22–80) after chemotherapy, and 87 months after surgery (IC95% 11-not reached, p 0.09). Seizure freedom was achieved in 6/15 (40%) patients following first salvage therapy (3 patients after surgery, 2 patients after chemotherapy, and 1 patient after radiotherapy). Conclusion: Reoperation aiming at total or near/total resection seems to offer a probability of a longer PFS and OS compared with the other treatment options. Seizure response may be achieved in a substantial proportion of patients receiving at tumor progression the different antineoplastic options.